Employee Demonstration and Policy on Setting the Minimum Wage for East Java Province from the Aspect of Industrial Relations - Sugianto, Giovanni; Eddy Madiono Sutanto (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
This research was conducted to determine industrial relations between the government, companies, and employees in determining the provincial minimum wage in East Java. This study uses a qualitative method.Data collection was carried out by interviews with the determination of three sources. Every aspect of industrial relations is used to see the role of each government agency, company, and employee. The validity of the findings istested using source triangulation, and then every aspect of industrialrelationsthat occursis described. The study results show that the industrial relations between the three parties were quite good. The government views the phenomenon of labor demonstrations as caused by several things, one of which is related to establishing the provincial minimum wage. Workers hold demonstrations every Labor Day and when setting wages. The government acts as a mediator between employers and workers during a demonstration. Then, the company experienced problems related to wages caused by several factors. Taxes in operational costs, shipping costs, and incidentals are one of the reasons. In addition, companies must also provide health insurance for workers in the social security program in accordance with government regulations. The labor association feels that the aspirations have not been realized, especially on the issue of wages. Therefore, workers hope for a proper discussion forum, and the aspirations conveyed can be realized, not just accommodated Keywords—Provincial Minimum Wage; Employees; Industrial Relations; Government; Companies; East Java